1989
DOI: 10.1021/bi00436a012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of [3H]muscimol binding to the GABAA receptor in bovine brain membranes

Abstract: The binding of the GABA receptor agonist [3H]muscimol to membrane preparations from bovine cerebral cortex has been investigated in equilibrium and kinetic experiments. Equilibrium binding curves are biphasic and suggest that [3H]muscimol binds to both high-affinity (Kd approximately 10 nM) and low-affinity (Kd approximately 0.5 microM) sites. Binding to each class of sites is inhibited by GABA and by the specific GABAA receptor antagonist bicuculline. The kinetics of [3H]muscimol binding have been measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Equilibrium (33) and carried out according to the method as described previously (4). Use of this system, in which the filter washing step was reduced to 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equilibrium (33) and carried out according to the method as described previously (4). Use of this system, in which the filter washing step was reduced to 0.…”
Section: Methodsmentioning
confidence: 99%
“…The GABA A R carries binding sites for a number of therapeutic agents including the benzodiazepines, barbiturates, neurosteroids, some general anesthetics, and possibly also alcohol (1). In brain membranes, there are at least two classes of binding sites for the endogenous neurotransmitter, which differ by more than an order of magnitude in their affinity for GABA or its structural analogues (2)(3)(4). This heterogeneity in binding was originally thought to reflect the diversity of GABA A R subtypes in brain tissue.…”
mentioning
confidence: 99%
“…Aliquots (0.35 mL) of nAcChR-enriched membranes were dialyzed against 0.35 mL of radiolabeled ligand solution with rocking for 6 h at 4°C. Total and free ligand concentrations were measured by taking duplicate 50 µL samples of each, adding 4 mL of hydrofluor (National Diagnostics) (DuPont, 1984;Agey & Dunn, 1989). DNPP-treated membranes were equilibrated with [ 3 H]AcCh or [ 3 H]SdCh by incubation for 30 min at room temperature.…”
Section: Preparation Of Nacchr-enriched Membrane Fragmentsmentioning
confidence: 99%
“…The number of agonist-binding sites on a single GABA A R has not been unequivocally defined, owing in large part to the inherent complexity of this receptor family. Early binding studies using native brain membranes suggested that there were at least two classes of binding sites of high (K D ϭ 10 -30 nM) and low (K D ϭ 0.1-1.0 M) affinity (11,13). Although these observations may have arisen from the heterogeneity of GABA A Rs that are now known to exist in mammalian brain, more recent studies using recombinant, presumably homogeneous, receptor subtypes suggest that individual receptors carry both high and low affinity sites for agonists (10,20).…”
Section: Rate Of Recovery Of Peak Amplitude As Function Of Timementioning
confidence: 99%
“…Radioligand binding studies have revealed the existence of (at least) two classes of agonist recognition sites on a single GABA A R (10), which differ in affinity by more than 1 order of magnitude (see also Refs. [11][12][13]. By using the recombinant rat ␣1␤2␥2 receptor expressed in tsA201 cells, we found two classes of binding sites for [ 3 H]muscimol with K d values of 8.1 and 430 nM (10).…”
mentioning
confidence: 99%